EVALUATION OF OCCUPATIONAL HEALTH AND SAFETY (OHS) ENVIRONMENTAL CONTROL IN THE EMERGENCY DEPARTMENT OF A REGIONAL HOSPITAL IN INDONESIA - Ahmad Farid; Indanah Indanah; Indarto Indarto; Hairil Akbar (Universitas Muhammadiyah Kudus, 2026)
The hospital environment and workplace safety support the quality of health care services provided to clients. The emergency department environment is characterized by high occupational risks, intensive work activities, high patient volumes, and exposure to numerous environmental hazards. The study aims to evaluate the control of the occupational health and safety environment in the emergency department of a regional hospital and its compliance corrections to Indonesian standards. The said study used a descriptive insights design conducted in the Emergency Department of a regional hospital in Pati, Indonesia, from January to March 2026. The parameters of the physical environment variables were temperature, humidity, noise, and lighting. Data collection involved direct insights, measurement of environmental variables using standard instruments, and interviews with key respondents selected through purposive sampling. The OHS manager is responsible for environmental health and OHS in the hospital. Data were analyzed descriptively by comparing measurement results according to the Indonesian Minister of Health Regulation No. 66 of 2016. The results describe environmental conditions that generally comply with national standards for hospital occupational safety. Room temperature at 25°C, humidity at 67.5 percent, noise level at 60 decibels, and lighting intensity up to 300 lux. On the other hand, operational issues were identified, including poor air circulation, increased room density during peak service hours, and psychosocial workload on health care workers. In conclusion, the study identified that the environmental control program in the emergency unit met Indonesian safety standards. To ensure a safe work environment and excellent service quality in hospitals, it is necessary to verify room ventilation, manage patient flow during peak hours, and provide stress management training for health care workers.